2021
DOI: 10.3389/fpsyg.2021.694122
|View full text |Cite
|
Sign up to set email alerts
|

Coping Strategy, Social Support, and Psychological Distress Among University Students in Jakarta, Indonesia During the COVID-19 Pandemic

Abstract: The COVID-19 pandemic has challenged the world for a year, where a study in China showed that the disease increased psychological distress among adolescents and college students, such as anxiety about the academic setback, economic effects, and impact on their daily life. However, a further study examining the impact of the disease on the mental health of students is required. Social support is the most vital psychosocial protective resource, where effective coping can reduce stress levels and prevent individu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 23 publications
1
24
0
5
Order By: Relevance
“…Our finding on support, coping and resilience during the pandemic explains how most students have managed to overcome the mental health challenges brought in by the pandemic. Previous studies have shown how optimism and positive coping (which in turn are related to higher social support) among students can prevent mental health problems or vice-versa [ 9 , 58 , 59 ]. Furthermore, our research demonstrates how support from personal tutors in difficult times can help students cope, not only with the academic pressures, but also with the emotional burden and stresses that they face in their personal lives.…”
Section: Discussionmentioning
confidence: 99%
“…Our finding on support, coping and resilience during the pandemic explains how most students have managed to overcome the mental health challenges brought in by the pandemic. Previous studies have shown how optimism and positive coping (which in turn are related to higher social support) among students can prevent mental health problems or vice-versa [ 9 , 58 , 59 ]. Furthermore, our research demonstrates how support from personal tutors in difficult times can help students cope, not only with the academic pressures, but also with the emotional burden and stresses that they face in their personal lives.…”
Section: Discussionmentioning
confidence: 99%
“…It is difficult to disentangle if the reportedly high impact of the COVID-19 pandemic on adolescents’ lives in Morocco and the USA is the main reason that these two countries’ adolescents also reported the highest level of psychological distress or that a higher “basic” level of psychological distress (mirroring cultural and national differences) may explain the two countries’ rankings. Other studies have focused on and investigated mediator variables, such as coping strategies, social isolation, social support from family and friends, access to the internet, and the use of social media, for their direct effect on adolescents’ psychological distress during the pandemic [ 65 , 66 , 67 , 68 ]. Li et al [ 69 ] showed that problem-based coping and online learning satisfaction fostered adolescents’ adjustment both directly and indirectly, serving as a buffer against the negative impact of stressors on adjustment.…”
Section: Discussionmentioning
confidence: 99%
“…Social support plays a fundamental role in people's well-being. In difficult times, such as in times of pandemic, social support works as an element of protection that helps individuals to cope with stressful situations more efficiently [43][44][45]. Having this support from family, neighbours or friends was another reason why people adhered more (12.8%).…”
Section: Discussionmentioning
confidence: 99%